Vital event of servise of Vicentas Sladkevičius in 1956-1959 - Grickevičius, Artūras (Genocidas ir rezistencija, 2021)
The article analyses in detail and gives a factual account of the particularly important period of ministry of the famous Lithuanian Catholic clergyman Sladkevičius, i.e. 1956–1959. The atheistic secular government exercised strict control and dictatorship over the most important affairs of the religious communities, dealt with the appointment of the clergy, and tried to turn the hierarchs into obedient followers of the government. The perseverance and efforts of Bishop Teofilius Matulionis, who survived the repression, made it possible for Father Sladkevičius, who was devoted to the Catholic Church, to become a bishop against the government’s wishes. The dissatisfied government tried to ignore the new bishop, and later to force him to cooperate. Not yielding to the pressure and temptations of the Red security agents and the Commissioner for Religious Cults, Sladkevičius, the Auxiliary Bishop of Kaišiadorys, remained faithful to the autonomy of the Catholic Church, and was therefore exiled to the periphery of another diocese, Panevėžys, as undesirable and dangerous. A full disclosure of these events is important for understanding the recent history of the Catholic Church in Lithuania and the Lithuanian unarmed resistance during the Soviet period.
Keywords: Catholic Church; soviet Lithuania; repressions; Vincentas Sladkevičius